Criminal minds. The eighth season [videorecording (DVD)] - Phillips, Mackenzie; Wayans, Kim; Wise, Ray, 1947-; Mantegna, Joe; Gibson, Thomas, 1962-; Gubler, Matthew Gray, 1980-; Cook, A. J., 1978-; Tripplehorn, Jeanne, 1963-; Moore, Shemar, 1970-; Vangsness, Kirsten, 1972- (Paramount Pictures, 2013)
Revolves around an elite team of FBI profilers who analyze the country's most twisted criminal minds, anticipating their next moves before they strike again. The Behavioral Analysis Unit's most prominent agent is David Rossi, a founding member of the BAU, who returns to help the team solve new cases, while pursuing some unfinished business of his own. Each member brings his or her own area of expertise to the table as they pinpoint predators' motivations and identify their emotional triggers.